2019
DOI: 10.1556/0806.47.2019.31
|View full text |Cite
|
Sign up to set email alerts
|

Auxin Induced Haploid Induction in Wide Crosses of Durum Wheat

Abstract: Doubled haploidy breeding via wide hybridization has been used in durum wheat haploid production for creating homozygosity in the shortest possible time. Post pollination treatment with hormones is a key factor for inducing haploid embryos in durum wheat wide crosses. An intergeneric hybridization experiment was carried out in seven durum wheat genotypes using Imperata cylindrica and two composites of Maize viz., Bajaura Makka and Early Composite, as pollen sources. The pollinated spikes were injected with 2,4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…As mentioned before, fertilization with alien pollen causes low embryo viability and zygote abortion during the initial stages of embryonic development. Post pollination application of PGRs, as a key step in chromosome elimination, can increase the recovery of haploid embryos to a state suitable for plant growth on nutrient media ( Mahato & Chaudhary, 2019 ). Wedzony et al (1998) found that dicamba and picloram were the most effective treatments for ovary growth and embryo production in triticale.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned before, fertilization with alien pollen causes low embryo viability and zygote abortion during the initial stages of embryonic development. Post pollination application of PGRs, as a key step in chromosome elimination, can increase the recovery of haploid embryos to a state suitable for plant growth on nutrient media ( Mahato & Chaudhary, 2019 ). Wedzony et al (1998) found that dicamba and picloram were the most effective treatments for ovary growth and embryo production in triticale.…”
Section: Discussionmentioning
confidence: 99%
“…In DH line production, developed zygotes have a very low viability, and most of them abort during the initial stages of development. The application of auxins induces ovary enlargement and enhances the growth of the haploid embryos to a stage that enables their culture onto nutrient media ( Laurie & Reymondie, 1991 ) (12–16 days post-pollination in wheat) ( Mahato & Chaudhary, 2019 ). There is a general agreement on the need for applying synthetic auxins in DH line production as a means of recovering haploid embryos especially to applying them following pollination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…homozygous pure lines from heterozygous breeding material in a generation (Yan et al, 2017). Improvements and the adoption of this technology have rendered it a rapid alternative to the conventional breeding methods and it has become an indispensable method to realize homogeneity in various studies and programs (Wędzony et al, 2009;Lantos & Pauk, 2016;Mahato & Chaudhary, 2019). The technology also contributes to more accurately assess QTL × environmental interactions (Yan et al, 2017) and has been applied in: genetic researches for marker-trait association study (Sorrells et al, 2011), genomics and as a target for transformation (Murovec & Bohanec, 2012), genetic engineering (Ravi & Chan, 2010), gene mapping (Hao et al, 2013), and mapping of quantitative trait loci (QTLs) (Shi et al, 2019).…”
mentioning
confidence: 99%
“…In cereal crops, the use of the doubled haploid (DH) technology enables genetically homozygous pure lines from heterozygous breeding material to be realised in a single generation (Yan et al 2017). Improvements and adoption of the technology have rendered it a fast alternative to conventional breeding methods and it has become a requisite tool in the attainment of homogeneity in different research and programmes (Wedzony et al 2009;Lantos & Pauk 2016;Mahato & Chaudhary 2019). The technology also aids in phenotyping more precisely (Yan et al 2017) and in genetic studies (Sorrells et al 2011;Hao et al 2013;Shi et al 2019).…”
mentioning
confidence: 99%